Learning styles and academic performance in EFL: An experimental study - Saritama Mora, Henry Javier (2003)
1. Theorethical framework concerning learing styles. 2. Description and application of instruments. 3. Presentation of results from instruments and analysis. 4. Practical suggestions and description of lesson plans. 5. Results of applying methods focusing on learning styles and analysis. 6. Conclusions and suggestions for further research